2011
DOI: 10.1503/cjs.005510
|View full text |Cite
|
Sign up to set email alerts
|

Information on the Internet for asplenic patients: a systematic review

Abstract: Background: Asplenic patients in general have poor knowledge about their condition. Patients are increasingly turning to the Internet for their health care information, therefore this is a resource that many asplenic patients will use. The aim of our study was to determine the quality of information on the Internet for asplenic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 14 publications
(8 reference statements)
1
12
0
1
Order By: Relevance
“…However, the operationalised subitems of the content guideline were not considered by the websites owners, in spite of having the highest rank (rank 1) and weighted multiplier (6) in the Bomba scoring system. The weakness in content and non-compliance with the standards of quality-assessment instruments were also indicated in other studies (3, 5, 8, 20, 25, 41, 42). Moreover, there was a negative, low, and significant correlation between content and availability guidelines; therefore, availability subitems such as the URL accessibility, home page load time, link checking and browser compatibility should be considered in addition to the procedures performed for content improvement.…”
Section: Discussionsupporting
confidence: 58%
“…However, the operationalised subitems of the content guideline were not considered by the websites owners, in spite of having the highest rank (rank 1) and weighted multiplier (6) in the Bomba scoring system. The weakness in content and non-compliance with the standards of quality-assessment instruments were also indicated in other studies (3, 5, 8, 20, 25, 41, 42). Moreover, there was a negative, low, and significant correlation between content and availability guidelines; therefore, availability subitems such as the URL accessibility, home page load time, link checking and browser compatibility should be considered in addition to the procedures performed for content improvement.…”
Section: Discussionsupporting
confidence: 58%
“…In 2004 Wallace et al 13 found that only 7% of the American Academy of Family Practice's PEMS were written below an 8 th grade reading level. Various subspecialties such as cardiology 14,15 , infectious disease, 16 plastic surgery, 17 dermatology, 18 orthopedics, 19,20 palliative care, 21 oncology 22,23 and obstetrics and gynecology 24,25 have studied the readability of the PEMs utilized in their fields, and findings consistently indicate that 9 th -12 th grade reading levels are necessary to read and comprehend these documents.…”
Section: Patient Education Materialsmentioning
confidence: 99%
“…After their visit, patients look for more detailed or reassuring information [ 20 ]. While this is an example of self-efficacy and therefore a potentially important source of patient empowerment, poor-quality information found online can lead to possible adverse effects [ 21 - 23 ]. In addition, there are concerns about the dangers of using the Internet to obtain medicines outside the official medical system [ 24 ].…”
Section: Introductionmentioning
confidence: 99%